ORIGINS OF CO2 IN PERMIAN CARBONATE RESERVOIR ROCKS (ZECHSTEIN, CA2) OF THE NW-GERMAN BASIN (LOWER SAXONY) - Fischer M.; Botz R.; Schmidt M.; Garbe-Schönberg D.; Rockenbauch K.; Glodny J.; Gerling P.; Littke R. (My University, 2006)
Permian carbonate reservoir rocks (Stassfurt-Carbonate) of the CO2-province (Lower Saxony Basin, NW Germany) are locally characterised by high amounts of CO2 leading to serious problems on exploration. In order to receive information on the major CO2 sources and CO2 migration and accumulation processes mineralogical, geochemical and stable isotope analyses (13C, 18O) were carried out on authigenic precipitations within the Stassfurt carbonate rocks (Ca2). These rocks contain early diagenetic (e.g., formed in soft sediment) carbonate minerals (calcite, dolomite) and anhydrite in concretions and small cracks. In addition, large (up to 2 cm wide) carbonate-cemented fractures formed in solid Ca2 rocks. Semi-quantitative estimates of the diagenetic mineral content showed variations between the investigated rock cores. Nine out of 12 Ca2 rock cores are derived from wells situated in the area of modern CH4-rich reservoirs and have distinct fracture systems developed. In contrast, the other three rock cores are from wells characterised by CO2-rich reservoirs and lack fractures of similar thickness. The assumed relationship between tectonically induced fractures and the gas content of the Ca2 reservoir rocks implies CO2 degassing of the Ca2 rocks at approximately 102 °C to ~150 °C (assumed δ18O porewater variation from 0‰ to +4‰ SMOW). REE distribution indicates at least three types of fracture- and crack-filling carbonates. Two carbonate generations formed from evolving diagenetic pore waters whereas one type reflects carbonate formation under hydrothermal influence. The ages of these cementations derived from Rb/Sr and U/Pb isotope analyses indicate their formation during late stage of/or after the inversion of the Lower Saxony Basin in Late Cretaceous times. The stable carbon isotope composition of the authigenic carbonate minerals reflects at least two carbon source endmembers available during diagenesis. Whereas many early-formed carbonates are related to the Permian 13C-rich carbon source, those carbonates which precipitated or recrystallised during early to late stage diagenesis and/or were induced by local tectonic events incorporated 12C-enriched CO2 from organic degradation processes. The stable oxygen isotope values of authigenic carbonates probably still reflect low temperatures of mineral formation from Permian sea water (as it is assumed for "non" recrystallised carbonates) or late-stage high-temperature (up to ~150 °C) precipitation from sea water-derived pore waters which may have been locally influenced by 18O-enriched fluids. However, most of the carbonate samples investigated are recrystallised (crystal enlargement of concretionary and fracture carbonate is observed) and hence, these carbonates are at least partly re-equilibrated (original 18O-content reduced) with surrounding pore waters at elevated temperature. Similar to the authigenic carbonate at least two sources may explain the concentration/carbon isotope relationship of modern CO2 present in the Ca2 reservoir rocks. An organic-derived CO2 endmember source (δ13C near - 20‰) is present in relatively low concentrations whereas large CO2 concentrations derived from an endmember source with an isotope value near 0‰. Although the latter source is unknown such "heavy" CO2 sources are most likely attributed to carbonate decomposition processes. © 2005 Elsevier B.V. All rights reserved.
Keywords: CARBON DIOXIDE; FRACTURE MINERALISATION; LOWER SAXONY BASIN; STABLE ISOTOPES; ZECHSTEIN CARBONATE; Мезозой::Меловая; Палеозой::Пермская; Mesozoic::Cretaceous; Paleozoic::Permian